PERANCANGAN AUGMENTED REALITY SEBAGAI MEDIA PENGENALAN BENDA BUDAYA - Sudarmanto; Edi Faizal (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2020)
Augmented reality (AR) as a technology enabler is becoming very popular in various fields such as education, design, navigation, and medicine. The aim of AR is to develop technology that allows real-time integration of digital content created by computers with the real world. Until now the development and introduction of tourism, especially sites and cultural objects in the village of Pleret is still not optimal. On the other hand, learning models in the introduction of culture and cultural objects that are commonly used today still use textbooks containing text and still images. Students tend to prefer playing gadged or mobile phones rather than learning with conventional methods because they tend to be boring and unattractive. One solution to overcome these problems is to use learning media that can display 3D objects in real-time. The application of technology using AR is expected to be able to provide motivation and enthusiasm for learning, so that the learning process becomes fun and the results of guarded learning will increase. This research will design an augmented reality technology design for the introduction of cultural objects in Pleret Village as an interesting learning media. The results of this study are in the form of AR application design which can be an interesting alternative learning media for introducing cultural objects in addition to being a means of cultural preservation as well as being a promotional media.